Readings In Popular Culture
XII, 235 p.
Keywords: This is the first book since Roland Barthes' Mythologies to take a comprehensive look at popular culture. The twenty-six essays in this volume, all written by specialists, cover a range of topics from t-shirts to computers. While each essay reflects some aspect of contemporary cultural theory, a number also develop original approaches to questions of whether popular culture is a condition or a representation of experience and how it manages to both resist and reproduce consumer capitalism. Together, these essays present an exciting reinterpretation of popular culture which will appeal to anyone interested in this important subject.